Technology-Supported Student-Centered Science Learning and Digital Competence Development in Upper Secondary Classrooms - Vo Doan Yen Nhi; Le Thai Minh Long (Three E Science Institute, 2026)
Digital competence is increasingly recognized as a core outcome of science education, yet evidence remains limited. This study examined whether technology-supported science instruction was associated with stronger multidimensional digital competence than conventional instruction and explored how seven competence dimensions were structurally related. A quasi-experimental pretest-posttest non-equivalent control group design was conducted with 180 Grade 11 students from four intact classes in two public schools. Over eight weeks, the experimental group engaged in inquiry- and project-based digital science learning, whereas the comparison group received instruction. Digital competence was assessed using a 28-item questionnaire and seven performance-based tasks. The experimental group showed larger gains across all dimensions, with significant baseline-adjusted differences across all outcomes (all p < 0.001) and moderate-to-large effects (partial η² = 0.26-0.29). More importantly, the pattern suggests that technology-supported student-centered science learning is associated not only with stronger technical performance but also with an integrated competence profile spanning information handling, data interpretation, communication, collaboration, problem-solving, creativity, and operational fluency. The structural findings further suggest that information literacy and digital communication may function as foundational competencies supporting analytical, collaborative, technical, and creative performance, with the strongest pathway from Digital Communication Skills to Collaborative Technology Use (β = 0.58). These findings imply that digital competence in science is best fostered when digital tools are embedded in inquiry, communication, collaboration, and production tasks rather than taught as isolated technical skills. Because the study involved only four intact classes, the findings should be interpreted as comparative and exploratory rather than definitive causal evidence.